Cooperation vs competition - Moore, Sarah (My University, 1894)
Introduction: As the years succeed each other with never varying regularity, so men come upon the earth, take the place assigned them by fate or destiny and begin the struggle for life. ‘Tis a strife from the cradle to the grave; each endeavoring to advance himself and those whom ties of kindred and affection have united with him. And what has been the result? War, the word that expresses to us more of cruelty, more of sorrow, more of bitter heart anguish than any word in human vocabularity, has been participated in by every nation in every age. In our social relations we call this hand to hand struggle another name—competition. This conflict may not be carried on by means of booming cannon, dealing vollies of shot and shell upon the forces arrayed against it; scenes of carnage on battlefields may not arouse our souls to its awful effects; the groans of wounded and dying may not ascend from the creatures prostrated by its action; but instead of the wounded soldier on the battlefield crying for water we may hear the voice of the victim of competition crying for bread. We may say what war with its glorious conquests its poets who have aroused men with the chance of which they sung; its heroic memories that have kindled the flame of patriotism in the hearts of succeeding generations has been an important element in developing our civilization, but we must all admit that there has been murder in its onward march.
Citation: Moore, Sarah. Cooperation vs competition. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Cooperation; Competition; War; Violence; Human nature; Sociology; Theses; Manuscripts (documents)